Positional Differences in GPS Outputs and Perceived Exertion During Soccer Training Games and Competition - Abbott, Will; Brickley, Gary; Smeeton, Nicholas J (Journal of strength and conditioning research, 2018)
Abbott, W, Brickley, G, and Smeeton, NJ. Positional differences in GPS outputs and perceived exertion during soccer training games and competition. J Strength Cond Res 32(11): 3222-3231, 2018-Soccer training games are popular training modalities, allowing technical, tactical, and physical aspects to be trained simultaneously. Small (SSGs), medium (MSGs), and large training games (LSGs) elicit differing physical demands. To date, no research has investigated physical and perceived demands of training games on soccer playing positions relative to competitive demands. In addition, previous research has referenced average competitive intensities, ignoring peak demands of competition. The current aim was to investigate the effect of training game formats on average and peak physical outputs produced by soccer playing positions. Physical and perceptual data from 22 competitive matches and 39 training game sessions were collected for 46 U23 professional players using 10-Hz global positioning system (GPS) and 100-Hz accelerometer devices (MinimaxX version 4.0; Catapult Innovations, Melbourne, Australia). Data analyzed included GPS-derived distance, speed, acceleration, deceleration, and rating of perceived exertion (RPE). Two-way between-subjects analyses of variance were used to compare average and peak GPS metrics, and RPE, between training games and competition for playing positions. Despite eliciting significantly higher average total distances compared with competition (p < 0.01), LSGs produced significantly lower peak total distance relative to the competition (p < 0.01). For very high-speed running and sprinting, LSGs elicited similar average intensities to competition; however, peak intensities were significantly lower than competition (p < 0.01). Medium training games and LSGs produced significantly higher average and peak moderate-intensity explosive distances than competition (p < 0.01). Results indicate the importance of analyzing relative to peak competitive demands, instead of focusing solely on average demands. The study demonstrates that specific game formats can overload the competitive demands of playing positions and provide an individualized training stimulus.